Evolução da cooperação em um caso particular do dilema do prisioneiro com três estratégias - Irene Edith Núnez Rodriguez (2015)
We develop the evolution of a population on infinitely repeated prisoner's dilemma (IRPD) with three reactive strategies ALLD, QTFT (almost TFT) and S(1; q), where the last one generalizes the generous strategy GTFT. It is shown the dynamic of those strategies when the prisoner's dilemma is played repeatedly using basic notions of game theory and qualitative analysis of ordinary differential equations on the plane.